Pediatric Palliative Care: Implications for Families and Caregivers - Chénard, Josée; Friedel, Marie; Olivier-d’Avignon, Marianne; Dubois, Anne-Catherine (Enfances, Familles, Générations, 2023)
Research Framework : This article proposes to define pediatric palliative care by adopting an approach centered on the family as a whole and on the various health professionals who support them. Objectives : The purpose of the introduction is to define pediatric palliative care, to describe the population likely to benefit from it, and to outline its primary effects on families as well as on caregivers. It also aims to contextualize each article in this issue. Methodology : The article is based on a review of the literature. Results : A definition of pediatric palliative care, of the population involved in it, and its consequences for the whole family. Conclusions : The authors suggest several areas for further research in the field of pediatric palliative care. Contribution : The article aims to stimulate reflection and to contribute to the advancement of knowledge in those working with children and their families in pediatric palliative care. At the same time, it introduces readers unfamiliar with it to this specific approach to care.